Ramucirumab plus paclitaxel as switch maintenance in patients with advanced HER2-negative gastric or gastro-oesophageal junction cancer: a cost-effectiveness analysis - Luo, Jiefeng; Li, Zhengxiong; Du, Qiong; Liu, Jiyong (Frontiers in Pharmacology, 2025)
ObjectivesThe ARMANI trial demonstrated that ramucirumab plus paclitaxel (switch maintenance group) significantly prolonged progression-free survival (PFS) and overall survival in patients with advanced HER2-negative gastric cancer (GC) and gastroesophageal junction cancer (GEJC) compared to continued first-line oxaliplatin-based chemotherapy (control group). However, its cost-effectiveness remained unclear. This study aimed to evaluate its cost-effectiveness from the Chinese and United States (US) healthcare system perspective.MethodsA partitioned survival model was developed to compare the total costs, quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios (ICERs) of switch maintenance group versus control group over a 10-year time horizon. Survival data were sourced from the ARMANI trial. Cost and utility were derived from open-access databases and published literature. The robustness of the results was verified through one-way sensitivity analysis and probabilistic sensitivity analysis (PSA). Additionally, subgroup analysis and scenario analysis were conducted.ResultsThe switch maintenance group yielded incremental gains of 0.15 QALYs in China and 0.16 QALYs in the US, with corresponding incremental costs of $56,738.32 and $185,250.55, resulting in ICERs of $373,219.84/QALY and $1,193,220.74/QALY, respectively. For the PD-L1 CPS ≥5 subgroup, incremental QALYs increased to 0.24 and 0.25, with incremental costs rising to $62,741.24 and $206,107.13, yielding ICERs of $266,259.94/QALY and $835,740.90/QALY, respectively. One-way sensitivity analysis revealed that the utility of PFS, the price of ramucirumab, and patient body weight were the most influential factors on the ICER, with consistent results observed from both Chinese and US perspectives. To be cost-effective in a 50% of chance, ramucirumab would need to reduce its price to 14.2% of the original price ($0.743 per mg) in China and 13.92% ($2.088 per mg) in the US, respectively.ConclusionRamucirumab plus paclitaxel is unlikely to be cost-effective compared to continuing oxaliplatin-based chemotherapy for patients with advanced HER2-negative GC or GEJC in China and US.